Pendapatan dan Risiko Produksi Usahatani Pacar Air (Impatiens balsamina Linn) pada Musim Hujan dan Kemarau di Subak Saradan, Desa Sibang Gede, Kecamatan Abiansemal, Kabupaten Badung - ADITYA, I MADE JUNI; WIDYANTARA, I WAYAN; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol 6 No 1 (2017)DO - 10.24843/JAA.2017.v06.i01.p15, 2017)
Income and Production Risk of Pacar Air (Impatiens balsamina Linn) Farm in Rainy and Dry Season in Saradan Subak, Sibang Gede Village, Abiansemal, Badung Regency Flower use rate in Bali equals to farmer’s interest to produce flowers. Thisphenomenon becomes the reason for Subak Saradan’s farmer trying changing thehalf of their field in rainy and dry season to plant impatiens flower in order to fulfilthe needs of market of their products.The aims of this research is to know which season are best to plant impatiensflowerobserved from the differences in income and risk in rainy and dry season. Variablesin this research are farming analysis and Subak Saradan’s risk level. These variablesare analysed using quantitative method. The result of this research shows that impatiens flower farming in dry season isbetter than in the rainy season. The income of the farmers in this season is Rp532,287,522. More than total income in rainy season that isRp 388,338,689. Indicator that is used to measure the risk level in rainy and dryseason in this research is variation coefficient with each values are 0.57 and 0.50.The value of the coefficient in rainy season is higher than the dry season. Hence, therisk of failing is higher in this season. This research also projecting the income of the farmers that are burdened withproduction risk level in the planting season. The average value of respondent’sincome based on their land size and risk of the seasons areRp 1,574,044.33 and Rp 3,601,044.01. In some condition with the highest risk, couldmake 20,9 % respondents in rainy season and 14,5 % respondents in dry season maysuffer loss.
Keywords: income, risk, rainy season, dry season